Intergenerational Social Mobility in Post-Reform Contemporary China - Leow, Antrusha (The Columbia Journal of Asia, 2022)
While post-1978 China has seen great socio-economic liberation of a large group of its people, this large nation is still known for its high levels of social inequality and extreme wealth discrepancy. Following the Xi administration’s recent efforts to address social inequality, this study investigates how levels of social mobility have changed since the Reform era and what are the predictors of social mobility in the new generation of Chinese using national microdata derived from the World Values Survey conducted in 2018. My analysis finds that changes in absolute mobility levels differ significantly along class lines, wherein agricultural workers have experienced an increase in upward occupational mobility into secondary sectors while class closure has taken root more deeply within the upper elites, creating a system of closed ranks. This can be largely traced back to two mechanisms: the decreasing significance of education as a social leveller and the rise in levels of status inheritance.